Microsoft Access 2000 Visual Basic for applications : fundamentals - Callahan, Evan, 1966- 4 0 16; 5 (Redmond, Washington : Microsoft Press, 1999)
Shows how to create database applications in Microsoft Access 2000, providing step-by-step lessons with examples from the business world, nineteen practice files on CD-ROM, and guidance on the development of three sample applications.
Developed learning tools--Cover.;Includes index.
Adult;Adult
Keywords: 2 -- 0; 6; Microsoft Access.;Microsoft Visual BASIC.;Microsoft Access.;Microsoft Visual BASIC; Database management.;Database management; 20; 2